The modern embroidery handbook : learn over 70 hand embroidery stitches step-by-step, plus 20 colourful projects and a sampler - Albans, Clare (White Owl, 2024)
"The Modern Embroidery Handbook is a perfect guide for stitchers of all levels, and is something you'll want to pick up from your bookshelf to refer to time and again. Inspired by vintage sewing companions, the follow up to Colourful Fun Embroidery contains step-by-step instructions for 72 different hand embroidery stitches, plus a large-scale sampler, alongside 20 brand new projects. Start with the basic ones most commonly found in embroidery designs, before experimenting with stitches for borders and edging, decorative stitches and motifs, as well as textural stitches and knots"--Publisher's description.